Assessment of Sulfide Concentration Effects in a Micro-Oxygenated Condition on the Growth and Removal by Pseudomonas putida (ATCC 49128) - Ahmad, Mani Malam; Abdul Aziz, Mohd Azoddein; Mior Ahmad Khushairi, Mohd Zahari; Mazrul Nizam, Abu Seman; Mohammad Saedi, Jami; Faten Ahada, Mohd Azli (Penerbit Akademia Baru, 2016)
Micro-oxygenation has recently being gaining popularity as a successful biological sulfide oxidation technique from inflicted wastewater. In this study the application of orbital shaker as an alternative digester for sulfi de bioxidation was experimented using Pseudomonas putida (ATCC 49128), under an oxygen tension or micro-oxygenated condition. Growth and sulfide reduction efficiency was measured spectrophotometrically under optimum physical conditions of pH, temperature, acclimatization time and agitation. Sulfide reduction was overwhelmingly recorded at three different sulfide loading rates of 200mM S2- L-1 d-1, 300mM S2 L-d-1 and 500mM S2-L-d-1 with corresponding appreciable cell growth measured at OD600nm. The obtained results indicated that it was possible to realized sulfide removal efficiency of 96% to 100% within 24hrs, as well 45% to 70% within the first 6hrs of inoculation, with an overwhelming removal of 100% after 18hrs in 200mM and 300mM. On the other hand, the corresponding growth was 3.00 OD600nm, 2.824 OD600nm and 2.456 OD600nm in 500pmm, 200ppm and 300ppm concentration respectively. Based on this finding, it was clear that this inoculum can be employed to treat sulfide contaminated wastewater even at higher range under micro-oxygena ted environmental condition.